Global networks - Holton, Robert J. (New York : Palgrave Macmillan, 2008)
In this sequel to Making Globalization, Robert Holton offers a thorough investigation of global network links across time and space. Exploring leading theory and new evidence on the subject, the book also offers advice on global network research. This is essential reading for all students of globalization and contemporary social change.
1 Introduction -- Making Globalization: Complexity, Human Agency and History -- Plan of the Book -- 2 Towards a Theory of Global Networks -- Manuel Castells and the Theory of Network Society -- Evaluating Castells -- Network Analysis, Networks as a Major Organizational Form and the Transition to Global Network Research -- Markets, Hierarchies and Networks -- Networks as a Distinct Organizational Form -- Linking Network Theories with Globalization -- Global Networks from Below -- Are 'Global Networks' Really Global? -- Conclusion -- 3 Methodologies of Global Network Analysis -- Global Network Research and Social Network Analysis -- Network Morphology -- Using Network Morphologies -- How Do We Know When a Global Network Exists? Some Quantitative and Qualitative Research Strategies -- Research in Multiple Settings -- Historical Sources on Global Networks -- Conclusion -- 4 Global Network Types -- Identifying Global Network Types -- A Compendium of Network Types -- Conclusion -- 5 On the Importance of Particular Persons -- In Search of Particular Persons -- Networks and Particular Persons: Some Sociological Themes -- The Uneasy Location of Particular Persons within Sociology -- Reputation and Networks: Some Introductory Issues -- Reputation through Global Networks of Particular Persons -- Friendship, Kinship and Sociability -- Conclusion -- 6 Global Networks and Cross-Cultural Engagement -- Some Introductory Issues -- Analysing Culture -- Problems with Essentialist Views of Culture -- Problems with Said's Critique of Orientalism -- Intercultural Engagement and the Place of Global Networks -- Intercultural Engagement and Empire -- Global Networks around Rabindranath Tagore -- The Emergence of a Global Public Sphere -- Beyond Elites and Leadership through Networks -- Conclusion -- 7 Politics and Global Networks -- Politics in Relation to Markets, Hierarchies and Networks -- Global Networks and Democracy -- Global Civil Society? -- Global Networks and Elites -- Global Networks, Democracy, and the Challenge of War and Conflict -- Conclusion -- 8 Prospects and Challenges -- Networks and Contemporary Society -- Network Challenges to State-Centric Organization -- Beyond a Top-down Approach to Networks -- What is Global about Global Networks? -- Methodological Glocalism -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: INTERNATIONALISM